Pengaruh Kompetensi Aparatur, Teknologi Informasi, dan Transparansi Terhadap Efektivitas Pengelolaan Dana Blud Puskesmas di Kabupaten Tuban - Sjarief Hidajat; Yesi Mariska (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
BLUD (Regional Public Service Agency) as a flexible approach in managing finances is expected to improve the provision of health services. However, the success of this plan depends on a number of factors. By examining the relationship between apparatus competency, information technology, and transparency, this research aims to reveal the effectiveness of financial management at the Tuban Regency Community Health Center. Primary data for this quantitative analysis comes from questionnaires given to Puskesmas employees in Tuban Regency who have BLUD status. To find out how the independent variables (apparatus competency, information technology, and transparency) relate to the dependent variable (effectiveness of BLUD fund management). Data was analyzed using Smart PLS using the Structural Equation Modeling (SEM) - PLS technique. The results of this research show that apparatus competency has no effect on the effectiveness of BLUD fund management, while transparency and information technology have quite a large influence. This shows that the ability of the apparatus is not the only determinant of the effectiveness of fund management. However, strong information technology and high transparency are very important to increase the effectiveness of managing BLUD Puskesmas funds.